The price of a constitution : - Kataoka, Tetsuya (Crane Russak, 1991)
An account of the origin of Japan's post-war regime and the way in which the United States was involved in its founding and the imposition of the "no war" constitution. The book argues that Japan's economic miracle has been one of revulsion against deprivation of political status symbolized by the constitution. The author also addresses United States foreign policy and Japan's trade problems with the US. The book is intended for the use of political analysts, economists and scientists.